Mental Health and Out-of-Schools Problems among Adolescents in Lagos State, Nigeria - Ahmed Ademola Oyeyemi; Prince Chiemeka Chukwudum; Ijeoma Okenwa-Fadele (Journal of Research in Education and Pedagogy, 2025)
Mental health and out-of-schools problems are related to an individual’s social and physical health and is of global priority. The mental health is the complete physical, social, and mental well-being of an individual. Adolescence, including the ages between 10 and 19 years, is the phase in which changes in mental health usually occur. Half of all mental health disorders begin by the age of 14 years, but most cases are not detected or treated at all. This study examined the mental health and out-of-schools problems among adolescents in Lagos State. Two research questions were formulated to guide the study. The survey research method was used to conduct the study. The target population of the study comprised of adolescents in Ajeromi-Ifelodun Local Government Area of Lagos State. One hundred (100) questionnaires were randomly distributed to the respondents and retrieved for data analysis. A self-developed questionnaire was used for the study. The bio-data of the respondents were analysed using simple percentage and frequency counts, while the stated research questions were analyzed using mean and standard deviation. The findings of the study include: the level of awareness of mental health and out-of-schools problems among adolescents in Lagos State on the high side; there are prevalence of mental health and out-of-schools problems among adolescents in Lagos State. Recommendations were made and they are: teachers should ensure in providing a friendly teaching and learning environment relaxed with low threat in order to ensure that learning is stress-free and also a core source of motivation; Teachers should ensure the usage of appropriate teaching strategies and techniques, enhance more collaborative relationship with their students and also provide basic facilities in schools including a serene atmosphere for learning; Secondary school authorities and teachers in Lagos should ensure comprehensive monitoring of adolescents within the ages of 12-15 years with utmost priority due to the prevalence of mental health issues among them, and also take stringent punitive measures in addressing truancy and bullying from senior students.